Anti-obesity Effect of Capsaicin in Mice Fed with High-Fat Diet Is Associated with an Increase in Population of the Gut Bacterium Akkermansia muciniphila - Shen, Wei; Shen, Mengyu; Zhao, Xia; Zhu, Hongbin; Yang, Yuhui; Lu, Shuguang; Tan, Yinling; Li, Gang; Li, Ming; Wang, Jing; Hu, Fuquan; Le, Shuai (Frontiers in Microbiology, 2017)
Capsaicin reduces body weight mainly through activation of transient receptor potential vanilloid 1 (TRPV1) cation channel. However, recent evidence indicates that the gut microbiota influences many physiological processes in host and might provoke obesity. This study determined whether the anti-obesity effect of capsaicin is related to the changes in gut microbiota. C57BL/6 mice were fed either with high-fat diet (HFD) or HFD with capsaicin (HFD-CAP) for nine weeks. We observed a significantly reduced weight gain and improved glucose tolerance in HFD-CAP-fed mice compared with HFD-fed mice. 16S rRNA gene sequencing results showed a decrease of phylum Proteobacteria in HFD-CAP-fed mice. In addition, HFD-CAP-fed mice showed a higher abundance of Akkermansia muciniphila, a mucin-degrading bacterium with beneficial effects on host metabolism. Further studies found that capsaicin directly up-regulates the expression of Mucin 2 gene Muc2 and antimicrobial protein gene Reg3g in the intestine. These data suggest that the anti-obesity effect of capsaicin is associated with a modest modulation of the gut microbiota.